Análise não linear de bielas isoladas de concreto em forma de garrafa deterioradas por reações internas de expansão. - Lira, Isaque de Souza (2020)
The research presents a discussion on the behavior of isolated concrete bottle-shaped struts affected by internal expansion reactions. The numerical modeling of concrete was performed with the Concrete Damaged Plasticity Model (CDPM) implemented in ABAQUS and the validation of the model was performed with Sankovich's tests (Sankovich, 2003). A procedure to automatically obtain the concrete plasticity and damage parameters necessary for the use of CDPM was developed in Matlab, based on the work of Alfarah (Alfarah et al, 2017), having as inputs the characteristic compressive strength of the concrete, the equivalent length of the finite element mesh and the ratio between the plastic and inelastic compressive strains. The results obtained showed that the CDPM is a model of plasticity with damage with the potential to represent the load-bearing mechanisms of isolated concrete bottle-shaped struts a range of several stress levels to which these elements may be subjected in the panels investigated. The numerical simulations for various levels of expansion were able to consistently represent the expected damage profile in the panels as well as the estimate of the first crack loading the crack opening and the value of the maximum possible force to be applied. For the panels investigated, the reduction observed in the failure load reached a value of 70%, the increase of the tensile plastic deformation was more than 60% and the maximum crack opening can reach an increase of 113%, when compared with those observed experimentally in panels without internal swelling reactions.